Genetic divergence in betelvine (Piper betle L.) - P Sunitha, B T Priya, P R Devi, (Journal of Spices and Aromatic Crops, 2013)
Genetic divergence was assessed in a population of 51 genotypes of betelvine (Piper betle) for seven characters using Mahalanobis D2 technique. The genotypes were grouped into six clusters. The clustering pattern of the genotype was random and did not follow geographical origin, indicating that geographical isolation may not be the only factor causing genetic diversity. Leaf area contributed maximum towards genetic diversity in betelvine. Cluster analysis revealed wide genetic distance between Cluster V and Cluster VI followed by Cluster IV and Cluster VI, and Cluster III and Cluster V. Thus, selections of parents from the clusters with high inter and intra cluster distance will help to obtain substantial heterosis in respect of economic traits during hybridization programme.